2021
DOI: 10.3389/fimmu.2021.689663
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of High ICAM-1 Level for Poor Treatment Response to Low-Dose Decitabine in Adult Corticosteroid Resistant ITP Patients

Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune hemorrhagic disease. Endothelial cell activation/injury has been found in some autoimmune diseases including SLE, systemic sclerosis, and rheumatoid arthritis, but its role in ITP pathogenesis remains unclear. This study attempted to elucidate the correlation between endothelial dysfunction and disease severity of ITP and find related markers to predict response to low-dose decitabine treatment. Compared with healthy volunteers, higher plasma levels of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Information, including demographic characteristics, clinical manifestations, bleeding scores, treatment and outcomes, were carefully recorded. Bleeding scores were rated according to the rating system for bleeding in ITP with slight modifications 1,20,21 . Information concerning age was excluded from the original scale in accordance with the protocol of different clinical bleeding systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information, including demographic characteristics, clinical manifestations, bleeding scores, treatment and outcomes, were carefully recorded. Bleeding scores were rated according to the rating system for bleeding in ITP with slight modifications 1,20,21 . Information concerning age was excluded from the original scale in accordance with the protocol of different clinical bleeding systems.…”
Section: Methodsmentioning
confidence: 99%
“…Bleeding scores were rated according to the rating system for bleeding in ITP with slight modifications. 1,20,21 Information concerning age was excluded from the original scale in accordance with the protocol of different clinical bleeding systems. Our experienced research team carefully scanned, interpreted, and doublechecked the data to ensure accuracy.…”
Section: Data Collectionmentioning
confidence: 99%
“…A before-and-after treatment study done with thrombopoietin-receptor agonists (TPO-RA) (romiplostim and eltrombopag) has identified that miR-199a-5p and miR-221-3p can predict platelet response to TPO-RA-treatment before treatment [ 156 ]. Recent research has investigated decitabine as a treatment for ITP [ 157 , 158 ]. Decitabine is a demethylating agent that in low doses is reported to have three functions: (i) promote megakaryocyte maturation and platelet production through demethylating hypermethylated promoters of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) gene [ 159 ]; (ii) restores expression of programmed cell death protein 1 (PD-1), by demethylating hypermethylated PD-1 promoter in CD8+ T cells, which inhibits cytotoxic T lymphocytes (CTLs)-mediated platelet destruction [ 160 ] and (iii) enhances Tregs and restores the balance of T helper cell subtypes through inhibition of STAT3 activation which decreases STAT3 and AKT phosphorylation [ 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the terms of endothelial function, bone marrow endothelial progenitor cells (BM EPCs) can improve hematopoiesis and megakaryocytopoiesis, and regulate thrombopoiesis ( 25 ). Correcting endothelial dysfunction added a promising tool to the treatment armory of corticosteroid-resistant ITP ( 26 ). Regarding the mechanism of IVIG treatment for ITP, interleukin (IL)-11 serves as a stimulating factor to increase platelets and other haemostasis factors (VWF and FVIII), which indicates that recombinant IL-11 (rIL-11) may be a promising substitute for IVIG ( 27 ).…”
Section: Pathogenesis Of Itpmentioning
confidence: 99%
“…Researchers first found endothelial cell alterations in a canine ITP model ( 112 ). Subsequently, it was found that corticosteroid-resistant ITP patients had endothelial dysfunction ( 26 ). Targeted improvement of endothelial cell function may offer new option for refractory ITP.…”
Section: Therapeutics Targeting Endothelial Cellsmentioning
confidence: 99%